1998
DOI: 10.1002/pen.10175
|View full text |Cite
|
Sign up to set email alerts
|

Performance of multilayer films using maleated linear low‐density polyethylene blends

Abstract: Blends of linear low‐density polyethylene (LLDPE) and linear low‐density polyethylene grafted maleic anhydride (LLDPE‐gMA) were prepared by melt mixing and then coextruded as external layers, with a central layer of polyamide (PA) on three‐layer coextruded flat films. Blends with contents of 0% to 55 wt% of maleated LLDPE, on the external layers, were analyzed. The T‐peel strength and oxygen and water vapor transmission rate of the films were measured. The surfaces of the peeled films were characterized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The finer structure (less roughness) of the latter indicates better role of the in situ compatibilizer to homogenize the blend 20. The rough surface of the blends is comparable to that found by Sanchez‐Valdes et al who showed an AFM micrograph of an extruded 15% LLDPE‐ g ‐MA film with an average roughness of 317.5 nm 26. The same trend is also found in several polymer blends by SEM study, where a finer structure is found for blends having compatibilizers 24–27.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The finer structure (less roughness) of the latter indicates better role of the in situ compatibilizer to homogenize the blend 20. The rough surface of the blends is comparable to that found by Sanchez‐Valdes et al who showed an AFM micrograph of an extruded 15% LLDPE‐ g ‐MA film with an average roughness of 317.5 nm 26. The same trend is also found in several polymer blends by SEM study, where a finer structure is found for blends having compatibilizers 24–27.…”
Section: Resultssupporting
confidence: 85%
“…The rough surface of the blends is comparable to that found by Sanchez‐Valdes et al who showed an AFM micrograph of an extruded 15% LLDPE‐ g ‐MA film with an average roughness of 317.5 nm 26. The same trend is also found in several polymer blends by SEM study, where a finer structure is found for blends having compatibilizers 24–27. More compatibilizer produces a finer structure 20, 28.…”
Section: Resultssupporting
confidence: 85%
“…Liquid-crystalline polymers also offer very low oxygen permeabilities, but suffer from their high price [37]. Multilayer films based on linear low-density polyethylene grafted maleic anhydride (LLDPE-gMA), coextruded with polyamide (PA) [38], and tailored blends, such as reactive blends of ternary blends composed of poly (vinyl-alcohol)/polyamide 6/poly(ethylene-co-ethyl acrylate) (PVOH/PA6/PEEA) [39], or blends possessing a process-induced laminar morphology [40,41] are devel- a Depends on crystallinity, orientation, and water vapor in case of polyamides [307]. b Depends on ethylene content.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting levels of only 1-2 wt% of MAH onto the polymer backbone are all that is typically required to produce excellent adhesion to the FBE primer [41]. Nonetheless, careful control is required at all times, particularly in the case of polypropylene, as chain scission can easily occur, decreasing molecular weight and reducing overall efficiency and hence performance [42,43].…”
Section: Chemistry and Synthesis Of Adhesivesmentioning
confidence: 99%